Картины русского мира: современный медиадискурс - Резанова З. И. Зоя Ивановна; Ермоленкина Л. И.; Костяшина Е. А.; Орлова О. В.; Катунин Д. А.; Мишанкина Н. А. Наталья Александровна (Томск, ИД СК-С, 2011)
В фонде НТБ ТПУ отсутствует